2000
DOI: 10.1002/(sici)1097-4555(200004)31:4<295::aid-jrs542>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and relaxation of benzonitrile and its clusters using time-resolved stimulated Raman-UV double resonance spectroscopy

Abstract: were observed by stimulated Raman-UV double resonance spectroscopy. Cluster structures were determined on the basis of the observed vibrational spectra, rotational contour analyses of the high resolution S 1 -S 0 electronic spectra and ab initio molecular orbital calculations with the HF/6-31G(d,p) basis set. It was found that the types of the cluster structures are classified into three groups. (1) The clusters with H 2 O, CH 3 OH and CH 3 CN represent the 'side'-type structure, in which the intermolecular bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 17 publications
1
25
2
Order By: Relevance
“…18,19 In the present work, we used two stimulated Raman pumping schemes depending on the energies of the vibrational levels. For the vibrations with their energies higher than 700 cm Ϫ1 , the lasers for stimulated Raman pumping were the second harmonic of an injection seeded Nd:YAG laser ͑Spectra Physics GCR-230-10͒ and the Nd:YAG laser pumped dye laser ͑Continuum ND 6000͒.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 In the present work, we used two stimulated Raman pumping schemes depending on the energies of the vibrational levels. For the vibrations with their energies higher than 700 cm Ϫ1 , the lasers for stimulated Raman pumping were the second harmonic of an injection seeded Nd:YAG laser ͑Spectra Physics GCR-230-10͒ and the Nd:YAG laser pumped dye laser ͑Continuum ND 6000͒.…”
Section: Methodsmentioning
confidence: 99%
“…This spectroscopy was first developed by Owyoung et al, [11][12][13] and was later modified to Raman dip spectroscopy with either ionization [14][15][16][17] or fluorescence detection. 18,19 Using this technique, many Raman active vibrations were observed and they were used for the determination of cluster structures.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…18 The S 0 state was determined to be C 2h symmetric, in agreement with earlier MP2/6-31G(d,p) ab initio calculations. 18,38 Schmitt et al found the excited state structure to be asymmetric and proposed that the excitation is localized on one of the BN monomers, supported by CIS calculations which also predict a nonsymmetric structure. 18 Pratt and co-workers 19 have also reported high-resolution LIF spectra of (BN) 2 , together with a structural analysis that is in agreement with that of results of Meerts and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…The (BN) 2 S 0 state geometry was optimized using the SCS-MP2 39 and SCS-CC2 40 methods with the aug-cc-pVDZ and aug-cc-pVTZ basis sets. Both optimizations yielded a C 2h symmetric structure, in agreement with earlier MP2 calculations with smaller basis sets, 38 and with the S 0 state rotational constants determined by the Schmitt and Pratt groups. 18,19 S 0 state normal-mode vibrational calculations were performed at the SCS-MP2/augcc-pVDZ level.…”
Section: Introductionmentioning
confidence: 99%